Pengaruh Lingkungan Kerja terhadap Disiplin Kerja Karyawan PT Hassco Multi Kimindo Sidoarjo - Dewi Andriani (Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2012)
The taking place of absent increase at PT. Hassco Multi Kimindo on January through August, 2010 from 2.5% to 3.3% was a phenomenon must be settled. The phenomenon was supported by data regarding the delay of project handling, in which on February the project handling was delayed for 4 days, on June it delayed for 6 days, and on August it delayed for 7 days. This research had the purpose to know the effect of work setting on working discipline at PT. Hassco Multi Kimindo of Sidoarjo.Data used in this research were primary data namely data were collected via questionnaire distributed to respondents that are the employees of PT. Hassco Multi Kimindo of Sidoarjo. Measurement scale used was the interval scale with measurement technique by level 1–7. The sampling technique was by the probability sampling exactly the simple random sampling (randomly sample taking) in which each of respondents meeting the population characteristic had the equal opportunity to be made as sample. Sample taking was based on the SEM assumption that the sample size was 5–10 times of estimated sample namely among 80–160.Keywords: Work Setting and Working Discipline